PROCESSES OF GLOBALIZATION AND TRANSNATIONALIZATION: THEORETICAL AND METHODOLOGICAL APPROACH TO COMPREHENSIVE EVALUATION - Rudenko-Sudarieva, Larysa; Mozhovyi, Oleh; Hurtov, Denys (Journal of European Economy, 2017)
Modern tendencies of world economy development are researched. The complex methods of working-out of description models of modern indicators, identified by authors as index of world transnationalization, index of total globalization and index of financial globalization and also an algorithm of their calculation and graphical interpretation is created. The authors’ methods of determination of developed indices of world transnationalization, total globalization, and financial globalization, which is on basis on comparative principles of theoretical generalization and improvement of key definitions and on generalization of conceptual approaches to prognosis of state of complex economic phenomenon are presented. Directions of improvement of appropriate methods of supporting of national safety on the basis of usage of formed by authors’ indices which provides the possibility to evaluate state of economic safety comprehensively and to give scientific credence the most favorable and safe script of integration process for Ukraine are proposed.